El pensamiento de J. M. Guyau y A. Fouillée en la filosofía peruana del siglo xix: la tesis doctoral de Ezequiel Burga (1898) en la UNMSM - Castro Dueñas, Julio César (2023)
The aim of this article is to show that prevailing ideas about the evolutionary process of life towards thought. in the thesis of Ezequiel Burga to opt for the degree of Doctor of Philosophy in 1898, reflects the variety of interpretations of the idea of progress, ranging from a Christian position to those related to positive philosophy. The combination of an eighteenth century that dismantles the traditions of ancient society, which borders on the divinization of reason, and before the vertiginous changes of science, technology and commerce of the nineteenth century are the background that allows the development of philosophical currents that in the late nineteenth century were part of the academic discussion, such is the case of thinkers such as Jean-Marie Guyau and Alfred Fouillée. On the other hand, E. Burga establishes a dialogue between these thinkers with Comte, Spencer and others, his hypothesis is that the positivist and idealist systems are two natural and necessary products of the human spirit. To support his position, he resorts to concepts of physics and biology, predicting different states of immortal consciousness without disappearing, a prelude to transhumanism and also of living cells combined with material elements, clearly a cyborg, in what would finally be a contemporary-scientific and evolutionary philosophical thought. The conclusion is that the theses of philosophy in the UNMSM of the nineteenth century welcomed the ideas of positive philosophy in vogue, focusing on the particular case of Guyau and Fouillée. It will highlight the authors and the categories they are using to place us in the context of their argumentation.